Philadelphia Paper - The Nickel Ores of Orford, Quebec, Canada - W. E. C. Eustis (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
In September last I had my attention called by Mr. R. G. Leckie to a deposit of nickel in the township of Orford, province of Quebec. In many ways it has proved to be a subject of great interest. As this ore is, as far as I can learn, entirely new in mineralogy and metallurgy, it has seemed to me that it would be a matter of interest to the Institute to have laid before it, in a short paper, the peculiarities I have met with in studying it. This deposit of nickel was first described by Dr. T. Sterry Hunt, our President, in the Geology of Canada, 1863, p. 738, in the follow ing terms: " The general diffusion of nickel throughout the magnesian rocks of the Quebec group has been already noticed. It has, however, never been met with in any considerable quantities in these rocks, although workable deposits of its ores may reasonably be looked for